The feasibility of targeting macrophage for disease treatment: roles of CEBPD - Fan, Tian; Lin, Shaoling; Zhou, Jingjing; Chen, Jia; Wang, Lexun (Frontiers in Immunology, 2025)
As ubiquitous innate immune cells, macrophages are crucial for tissue homeostasis and disease pathogenesis. Although our understanding of macrophage subsets and functions has advanced, no effective strategies are available for targeting macrophages to treat diseases in clinical settings due to their heterogeneity. Transcription factors that regulate macrophage function have received increasing attention. CCAAT/enhancer-binding protein delta (CEBPD), an inflammation-associated transcription factor characterized by low basal expression but rapid induction by stimuli, has emerged as a key regulator of macrophages. CEBPD governs diverse biological processes in macrophages through its target genes. Furthermore, macrophage CEBPD significantly contributes to various pathologies. Modulating CEBPD expression or activity in macrophages could regulate various molecular processes to improve disease progression and alleviate organ damage; therefore, novel CEBPD-based therapeutic methods for treating diseases have attracted attention. In this review, we describe the factors upstream and downstream of CEBPD in macrophages. We then summarize recent advances in the regulation of macrophage biological processes by CEBPD. Finally, we discuss the contribution of macrophage CEBPD to various diseases and highlight strategies for developing novel therapies to modulate macrophage function by targeting CEBPD.